Aspects of Employment in Ottoman Waqfs Examples of Fatih, Yavuz Selim, and Süleymaniye Waqfs - Ayşenur Karademir (İstanbul İktisat Dergisi)
This study examines the role of Ottoman imperial waqfs as employment institutions, focusing on the salary register EV.HMH.1178, prepared for the Fatih, Yavuz Selim, and Süleymaniye waqfs in the early 18th century. By analyzing the administrative and financial oversight documented in this register, the article explores the redistributive functions of these waqfs and their contribution to sustaining long-term social and economic stability. Special attention is given to the intervention of the central office (Sadr-ı Âli Nezareti/Grand Vizier’s Office) through an imperial decree and the classification of employee roles by workplace. This research contributes to the literature on waqfs by providing insights into their employment systems and administrative practices.